Transcription factor Creb3l1 maintains proteostasis in neuroendocrine cells - Greenwood, Mingkwan; Gillard, Benjamin T.; Farrukh, Rizwan; Paterson, Alex; Althammer, Ferdinand; Grinevich, Valéry; Murphy, David; Greenwood, Michael P. (Molecular metabolism, 2022)
Dynamic changes to neuropeptide hormone synthesis and secretion by hypothalamic neuroendocrine cells is essential to ensure metabolic homeostasis. The specialised molecular mechanisms that allow neuroendocrine cells to synthesise and secrete vast quantities of neuropeptides remain ill defined. The objective of this study was to identify novel genes and pathways controlled by transcription factor and endoplasmic reticulum stress sensor Creb3l1 which is robustly activated in hypothalamic magnocellular neurones in response to increased demand for protein synthesis.
Online verfügbar: 6 July 2022, Artikelversion: 15 July 2022
Gesehen am 11.01.2023